2022
DOI: 10.3991/ijim.v16i05.28129
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mobile-Assisted Language Learning Research Trends and Practices in Malaysia

Abstract: Mobile technology integration in Malaysia’s English language education has a bright future, owing to the many advantages offered by mobile devices. However, there are inadequate studies that systematically review existing work in Malaysia to uncover gaps in the use of mobile technologies for English teaching and learning. Thus, a systematic review was conducted to offer an up-to-date synthesis of Mobile-Assisted Language Learning (MALL) integration in Malaysia from January 2019 to January 2021. The review foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The second criterion was the timeline, which was within 2011-2020 (a span of 10 years), that essentially helped the researchers to focus on relevant and recent articles on Augmented Reality research, which also helped highlight the evolution of such a novel technology. In addition, [33] stated that it is very impossible for researchers to evaluate all published articles; as a result, researchers should determine the time period within which they will analyse and submit their review findings properly.…”
Section: Inclusion (Eligibility) and Exclusion Criteriamentioning
confidence: 99%
“…The second criterion was the timeline, which was within 2011-2020 (a span of 10 years), that essentially helped the researchers to focus on relevant and recent articles on Augmented Reality research, which also helped highlight the evolution of such a novel technology. In addition, [33] stated that it is very impossible for researchers to evaluate all published articles; as a result, researchers should determine the time period within which they will analyse and submit their review findings properly.…”
Section: Inclusion (Eligibility) and Exclusion Criteriamentioning
confidence: 99%
“…Mobile learning is part of Mobile-assisted Language Learning (MALL) that has advanced with a growing number of studies that explore its various uses, both in and out of formal language classes [11], [12], [8]. Interestingly, mobile learning constitutes the prominent and popular form of 21st century student-centered learning applications worldwide [13].…”
Section: Mobile Learning Trends In English Language Classroomsmentioning
confidence: 99%
“…It is essential to determine the emphasis on any particular education levels of the respondents in language-related educational studies, as suggested by [8] to observe their differential implications, particularly in relation to this review. Besides, the respondents involved in the studies are sometimes not explicitly acknowledged as users of mobile learning platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been reading and writing in digital format which could allow them to enhance new literate skills and abilities to learn content concepts. It has been, also, reported that young adults could perform academic task better if they learnt through the internet, meaning that acquiring knowledge in a formal classroom will be less likely effective than that of conducting in the virtual classroom [2]. The youth report also shared the feeling of not being up to date from academic learning when teachers failed to spend their funds of knowledge of digital literacies [3].…”
Section: Introductionmentioning
confidence: 99%